(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
In the current work the investigation of interaction between polyguanylic acid and ethidium bromide (EtBr) at different ionic strengths and at three different temperatures has been carried out. Based on absorption spectra of formed complexes, adsorption isotherms were constructed and binding constants were determined. Thermodynamic parameters of this interaction were determined as well. Obtained data show that in four-stranded structure, the “classical” intercalation becomes impossible and the only possible binding mode remains semiintercalation. It was also shown that thermodynamic parameters of interaction by semi-intercalation mode do not strongly depend on the ionic strength of solution.